(3TQM bhGYO GdCMcGes - (3GdcQcj GdYGedj, CHh GdMSf, GdeMbb GdKGfj, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj GdcQcj GdYGedj, J (B940(3g` (B1534(3es ((3OGQ Gdehecj OGTGgs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3bhdg(B: (3GdeMV GdKGdK aj GdEbQGQ, hajg aUhd, GdChd aj CQcGfg(B: (3hajg eWGdH, GdChd(B: .. (3GdCbQGQs
(3BNQgG (B:s
(3BNQgG(B: (3hGdMGUd Cf EWdGb GdGSJJGHI aj MGd GdMjGI hgj GdJhcjd hdG jMed Ydi (B.. (3EdG HOdjd jOd Ydi Cf GdJUQa HYO GdehJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 281s
(3GdPQjYI, L(B5: 51s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis